Between Ideologies and a Hard Place: Hans Magnus Enzensberger's Utopian Pragmatist Poetics - Jonathan Monroe (Studies in 20th & 21st Century Literature, 1997)
The marginalization of poetry in North American culture makes it difficult to appreciate fully on this side of the Atlantic the importance of Hans Magnus Enzensberger's literary and cultural contributions over the past four decades. Working against familiar cultural encodings that would align poetry uncritically with the "personal" and prose with the "political," his oeuvre makes a strong case for poetry and critical prose as vitally complementary activities. In his 1991 collection of poems, Zukunftsmusik (Future Music) and his 1993 prose collection, Civil Wars: From L.A. to Bosnia, Enzensberger renews his longstanding commitment to "the process / of becoming human." Taken together, the two collections suggest the importance of maintaining connections across genres and their constituencies. In the context of the chaotic civil wars and "great migrations" that have shaped global culture since 1989, Enzensberger's thoroughgoing attention to internal differences within language and culture offers a model of hopeful resistance to an increasingly unreflective culture. His recent writing calls us to look carefully into what poetry will become, and for whom, in the wake of 1989.
Keywords: ideologies; North American; culture; marginalization; poetry; Atlantic; Hans Magnus Enzensberger; literary contributions; cultural contributions; cultural encodings; personal; prose; political; oeuvre; critical prose; complementary; Zukunftsmusik; Future Music; Civil Wars: From L.A. to Bosnia; & quot; the process / of becoming human& quot; connections. genre; constituencies; chaotic; civil wars; global culture; 1989; language